A Metro Freight Plan for Mixed Passenger and Freight Transportation - Yutao Ye; Junhua Guo; Lixin Yan (Journal of Advanced Transportation)
This study proposes a metro freight plan for mixed passenger and freight transportation. First, this study explores the problem of single-line metro train service under mixed passenger and freight transportation. Then, comprehensively considering the constraints of metro train freight capacity, loading and unloading time, and train schedules, a metro freight service model was established, and an efficient and accurate train schedule and freight distribution plan were developed to minimize metro freight costs. Finally, through actual case studies, an improved variable neighborhood search algorithm (VNS) was used to verify the effectiveness of the model, and the sensitivity of different train capacities, train headway, and cargo operation cost to the cost of metro freight was also discussed. The cost of cargo operation is the main factor that affects the cost of metro freight. The metro freight plan proposed in this study can provide decision support for the setting of train schedules and freight distribution plans.